Bioethics and Biolegal: ways to fully reconcile human beings - Gamboa-Bernal, Gilberto Alfonso (Universidad Hemisferios, 2024)
Although Bioethics was born in a context of biomedical research and the practice of health sciences, it was not its only course: VR. Potter proposed a global bioethics, where the environment should also be the protagonist. And if one of the tasks that Bioethics has had since its origins is to return to the practice of medicine the human component that biotechnological developments threaten to take away, Bioethics must also serve to reconcile the human being with himself, with others and with the environment of which it is a part, since it intervenes and modifies it with a negative balance for nature. Another main task of Bioethics is to contribute to recognizing the value of human life and strengthening a culture of life, which armed conflicts and economic interests seek to make disappear. To achieve these objectives, a convenient biolegal support is necessary, of which the legislative bodies are especially guarantors, who have a precise and clear responsibility to legislate in accordance with the Political Constitution of the States. It is important and essential that new generations acquire, from an early age, concepts, habits and attitudes that guarantee a wisdom of life that is reflected in everyday life, where goods, virtues and norms are articulated that guarantee human coexistence and the consolidation of societies. fair, supportive and truly free.